Polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel and its application

By blending polyacrylamide with sodium alginate and compounding polypyrrole, a composite conductive hydrogel with high flexibility, high strength, high stretchability, high conductivity and biocompatibility was prepared, which solved the problem of lack of suitable materials in the prior art and achieved sensor applications with high sensitivity and stability.

CN116239802BActive Publication Date: 2025-03-18ZHEJIANG SCI-TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310378835.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-03-18
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

There is a lack of a material with high flexibility, high strength, high stretchability, high conductivity and biocompatible in existing flexible wearable devices, for assembling flexible sensors to detect human joint movement and health monitoring.

Method used

Dual network hydrogels are prepared by blending polyacrylamide with sodium alginate, and by composite polypyrrole, a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel with high flexibility, high strength, high stretchability, high conductivity and biocompatibility are formed.

Benefits of technology

The composite conductive hydrogel exhibits high sensitivity, high stability and fast response capabilities in the sensor, and can effectively detect deformation and be applied to human movement and health monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239802B_ABST
    Figure CN116239802B_ABST
Patent Text Reader

Abstract

The present invention discloses a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel and its application. The present invention adopts a one-pot method to synthesize polyacrylamide-sodium alginate hydrogel, and dopes pyrrole into the composite hydrogel by dipping, and then oxidizes pyrrole by ferric chloride solution, and polymerizes it into polypyrrole in situ by the molecular template effect of sodium alginate, and the obtained polypyrrole nanospheres are evenly dispersed in the hydrogel matrix, and finally obtains a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel with good conductivity, ultra-high tensile performance, high strength, high toughness, good biocompatibility, certain self-repair and self-adhesion ability. The composite conductive hydrogel of the present invention can be used to prepare a tensile strain sensor, which has the characteristics of high sensitivity, rapid response, large detection range, etc. The present invention is simple to operate and concise in steps, and is suitable for multiple related fields such as human motion detection, vocalization monitoring, and electronic skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible wearables, and in particular relates to a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel and an application thereof. Background Art

[0002] With the rapid development of science and technology, smart wearable devices have gradually become popular. The application of flexible wearable electronic devices in health detection, motion detection, electronic skin and other fields has also attracted much attention. Flexible sensors, as an important component of flexible wearable devices, are the key areas of related research. At present, there is an urgent need for a new type of flexible conductive material for assembling flexible sensors for detecting human joint movements, health monitoring and other applications.

[0003] Since flexible wearable devices are mainly used on the human body, they have high requirements for the flexibility, stretchability and biocompatibility of the materials used. Conductive hydrogels have advantages such as excellent flexibility and conductivity, and have great development potential in the field of flexible wearable electronic devices.

[0004] Currently, common conductive hydrogels are mainly divided into two types: synthetic polymers and natural polymers. Polyacrylamide is a common synthetic polymer material, which is often used to prepare hydrogels. It has excellent flexibility, tensile deformation ability and biocompatibility, but its tensile strength is relatively poor.

[0005] Based on the defects of the prior art, the present invention prepares a double network hydrogel by blending polyacrylamide and sodium alginate, a natural biomaterial, to improve the mechanical strength of the hydrogel, and obtains a composite conductive hydrogel with high flexibility, high strength, high stretchability, high conductivity and biocompatibility by compounding polypyrrole. The composite conductive hydrogel is applied to sensors and has the advantages of sensitivity, high stability and rapid response. Summary of the invention

[0006] The object of the present invention is to provide a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel and its application. The composite conductive hydrogel of the present invention has the advantages of high flexibility, high strength, high stretchability, high conductivity and biocompatibility. In addition, when the composite conductive hydrogel is applied to a sensor, its resistance change rate is linearly related to the strain rate, and it has the advantages of high sensitivity, high stability and rapid response.

[0007] The first object of the present invention is to provide a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel, which is prepared by the following steps:

[0008] 1. Preparation of polyacrylamide-sodium alginate composite hydrogel

[0009] Dissolve acrylamide and N, N-methylenebisacrylamide in a glycerol aqueous solution. After the acrylamide and N, N-methylenebisacrylamide are completely dissolved, add sodium alginate to the aqueous solution, stir until completely dissolved, then add ammonium persulfate and tetramethylethylenediamine, stir evenly and ultrasonically treat, then place in an oven at 50-65° C. for reaction for 1-1.5 hours to obtain a polyacrylamide-sodium alginate composite hydrogel;

[0010] 2. Preparation of polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel

[0011] The composite hydrogel is immersed in pyrrole monomer at 2-5°C for 20-30 hours, and the pyrrole monomer completely penetrates into the hydrogel; the hydrogel is then immersed in ferric chloride solution for 10-15 hours, and the temperature is maintained at 2-5°C. During this process, pyrrole is 3+ The ions were oxidized and polymerized into polypyrrole, and a physical cross-linking structure was formed between Fe ions and sodium alginate. Finally, the residual liquid and impurities on the surface of the hydrogel were washed with deionized water to obtain a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel.

[0012] Furthermore, the mass ratio of acrylamide, N,N-methylenebisacrylamide, glycerol and water is 10-30:0.01-0.15:0-50:100.

[0013] Furthermore, the amount of sodium alginate used is 0.5-3wt% of the aqueous solution.

[0014] Furthermore, the dosage of the ammonium persulfate is 0.05-0.5 wt % of the acrylamide.

[0015] Furthermore, the amount of tetramethylethylenediamine used is 0.05-0.3 vol% of the aqueous solution.

[0016] Furthermore, the amount of pyrrole used is 0.5-10 vol% of the volume of the hydrogel.

[0017] Furthermore, the concentration of the ferric chloride solution is 0.5-2 mol / L.

[0018] The present invention prepares a double network hydrogel by blending polyacrylamide with sodium alginate to improve its mechanical strength, and sodium alginate has excellent biocompatibility. In addition, as a nanomaterial, how to evenly disperse polypyrrole is a research difficulty, and sodium alginate contains a large number of hydroxyl functional groups, which can produce hydrogen bonds with the amino groups of polypyrrole, so that polypyrrole is adsorbed on the molecular chain of sodium alginate and forms a Fe 3+ Ionically physically cross-linked alginate-polypyrrole three-dimensional conductive network.

[0019] The second object of the present invention is to provide an application of the above-mentioned composite conductive hydrogel in a sensor, and the specific steps include: cutting the conductive hydrogel into a suitable size, connecting copper wires at both ends with conductive silver glue, connecting the copper wires to a digital multimeter to measure resistance, attaching and fixing the hydrogel to a part to be tested, and testing the change in resistance of the conductive hydrogel with the movement of the test part.

[0020] Furthermore, the part is a part where deformation and movement are obvious; further, the part includes any part of the fingers, wrists, elbows, knees and throat.

[0021] The working principle of the present invention is: when the composite conductive hydrogel is stretched, the conductive network will be gradually straightened and accompanied by the breaking of a small amount of ionic bonds. In this process, the resistance of the hydrogel will gradually increase, and the resistance change rate is linearly related to the strain rate; when the strain increases to a certain extent, the ionic crosslinking effect in the hydrogel will be completely broken, and the stretching will continue at this time. The distance between the sodium alginate-polypyrrole conductive units will gradually increase, and the resistance of the hydrogel will increase faster. The resistance change rate is still linearly related to the strain rate, but the slope of the linear relationship is significantly improved compared to the first stage. The ratio of the hydrogel resistance change rate to the strain rate is its sensitivity (gauge factor, GF). Since the physically crosslinked sodium alginate-polypyrrole conductive network is rigid, when the hydrogel is deformed, even a very small deformation will affect the rigid conductive network and change the resistance of the hydrogel, which gives the conductive hydrogel high sensitivity and rapid response capability. On the other hand, this physically crosslinked conductive network can be reorganized. No matter how much damage occurs, the conductive network will be re-formed after the stress is removed, which gives the hydrogel sensor excellent stability.

[0022] The beneficial effects of the present invention are:

[0023] (1) The present invention synthesizes a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel. Polyacrylamide, as a chemically cross-linked polymer network, serves as the framework of the composite hydrogel, giving it excellent tensile properties. Polypyrrole, as a conductive polymer, has excellent conductivity, but it has obvious hydrophobicity and is not easy to disperse in hydrogels, which limits its application in conductive hydrogels. Sodium alginate, as a natural biopolymer, has hydroxyl groups on its molecular chain that can combine with the amino groups of polypyrrole, and acts as a carrier to help polypyrrole be evenly dispersed in the hydrogel.

[0024] (2) The present invention uses polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel to assemble a tensile strain sensor. The sensor has excellent sensitivity, wide measurement range and excellent stability.

[0025] (3) The present invention is easy to operate, and the prepared hydrogel sensor can realize efficient detection of deformation and can be used for monitoring human movement, health, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart for preparing the polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel.

[0027] Figure 2 This is the sensitivity (GF) curve of the hydrogel sensor.

[0028] Figure 3 500 cycles test of the hydrogel sensor under 50% strain condition.

[0029] Figure 4 are the response time and recovery time of the hydrogel sensor.

[0030] Figure 5 Sensing curve of the hydrogel sensor used to monitor the finger movement amplitude.

[0031] Figure 6 Say "Hello" to the hydrogel sensor monitoring subject.

[0032] Figure 7 Say "Thankyou" to the subjects monitored by the hydrogel sensor. DETAILED DESCRIPTION

[0033] In order to make the technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] Example

[0035] First, prepare polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel (flow chart as shown in Figure 1 (shown)

[0036] Dissolve 1.75g ​​acrylamide in 10vol% glycerol solution, add 0.003g N,N-methylenebisacrylamide, add 0.15g sodium alginate after it is completely dissolved, and stir until it is completely dissolved. Add 0.004g ammonium persulfate and 0.01ml tetramethylethylenediamine, stir evenly and ultrasonically treat, then place in an oven at 60℃ for 1 hour to react to obtain a polyacrylamide-sodium alginate composite hydrogel, which is immersed in 0.2ml of pyrrole monomer at 4℃ for 24 hours. During this process, the pyrrole monomer completely penetrates into the hydrogel. The hydrogel is immersed in a 1M concentration of ferric chloride solution for 12 hours, the temperature is maintained at 4℃, the molar ratio of ferric chloride to pyrrole is 3:1, and the pyrrole is Fe3+ Ion oxidation polymerization to polypyrrole, and Fe 3+ A physical cross-linking structure is formed between the ions and the sodium alginate. The residual liquid and impurities on the surface of the hydrogel are washed with deionized water to obtain a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel.

[0037] Second, testing the performance of hydrogel-based tensile strain sensors

[0038] The polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel was cut into a rectangle of 50 mm × 10 mm × 1 mm. The two ends of the hydrogel were connected to a digital multimeter with copper wires. The conductive hydrogel was stretched at a speed of 50 mm / min using a universal testing machine to measure the resistance change of the hydrogel. The sensitivity (gauge factor, GF) of the hydrogel sensor is the ratio of the resistance change rate to the tensile strain rate, as shown in Figure 2 The figure shows the relationship curve between the resistance change rate and the tensile strain rate of the polyacrylamide-sodium alginate-polypyrrole hydrogel sensor. It can be clearly observed that the resistance change rate of the sensor has a good linear relationship with the tensile strain rate, and is divided into two parts: in the strain range of 0-400%, the sensitivity of the sensor is 1.89, and the fitting degree is 99.0%; in the strain range of 400-800%, the sensitivity is 4.53, and the fitting degree is 99.4%. In the polyacrylamide-sodium alginate-polypyrrole conductive hydrogel, there is a three-dimensional conductive network of sodium alginate-polypyrrole that runs through its structure. When the hydrogel is stretched, the conductive network is gradually straightened, accompanied by a small amount of physical cross-linking breaking, and the resistance of the hydrogel increases. This stage corresponds to the first part of the sensitivity curve of the hydrogel sensor. When the tensile strain rate increases to 400%, a large number of physical cross-linking breaks occur in the hydrogel, and the sodium alginate-polypyrrole conductive network is completely destroyed. At this time, when strain is applied to the hydrogel, the distance between the sodium alginate-polypyrrole conductive units will increase accordingly, and the resistance change of the hydrogel will become more obvious. This process corresponds to the second part of the hydrogel sensor sensitivity curve.

[0039] Under the test condition of 50% strain, the hydrogel sensor was subjected to 500 cycles of testing to test the stability of the hydrogel sensor. Figure 3 As shown, from Figure 3 It can be seen that the sensitivity of the conductive hydrogel of the present invention did not change after 500 cycles under the test condition of 50% strain, and it has high stability. The response speed of the hydrogel sensor was tested. The hydrogel sensor was quickly stretched to a 10% deformation state, kept for a period of time, and then quickly restored to the original state. The response time and recovery time of the hydrogel sensor were tested. The results are as follows: Figure 4As shown, the results show that the response time and recovery time of the polyacrylamide-sodium alginate-polypyrrole hydrogel sensor are 112ms and 103ms, respectively.

[0040] Third, the hydrogel-based sensors are used for actual human testing

[0041] The hydrogel sensor is fixed on the finger. During the measurement process, the finger is gradually bent into different angles and restored. The finger stays at each angle for 5 seconds. The sensing curve of the hydrogel sensor is recorded, such as Figure 5 As shown, it can be observed that the resistance of the hydrogel sensor increases with the bending of the finger and decreases with the recovery of the finger. When the finger is in a fixed state, the resistivity change curve of the hydrogel sensor shows a flat platform, and the resistance in each fixed stage during the bending process is roughly the same as that in the recovery stage, proving that the hydrogel sensor can monitor the changes in the bending angle of the finger joints in real time.

[0042] The hydrogel sensor was fixed on the subject's throat, and the sensing curve was recorded when the subject said words such as "Hello" and "Thank you". Figure 6 and Figure 7 As shown, the results show that the hydrogel sensor can monitor weak signals such as swallowing and speaking in real time, and the test results have good repeatability.

[0043] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.

Claims

1. A polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel, characterized in that: Prepared by the following steps:

1. Preparation of polyacrylamide-sodium alginate composite hydrogel Acrylamide and N, N-methylenebisacrylamide are dissolved in a glycerol aqueous solution, and then sodium alginate is added to the aqueous solution, stirred until completely dissolved, and then ammonium persulfate and tetramethylethylenediamine are added. After stirring evenly and ultrasonic treatment, the mixture is placed in an oven at 50-65°C for reaction for 1-1.5 hours to obtain a polyacrylamide-sodium alginate composite hydrogel; the mass ratio of acrylamide, N, N-methylenebisacrylamide, glycerol and water is 10-30:0.01-0.15:0-50:100; the amount of sodium alginate is 0.5-3 wt% of the aqueous solution; the amount of ammonium persulfate is 0.05-0.5 wt% of the acrylamide; and the amount of tetramethylethylenediamine is 0.05-0.3 vol% of the aqueous solution.

2. Preparation of polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel The composite hydrogel is immersed in pyrrole monomer at 2-5°C for 20-30 hours; the hydrogel is then immersed in ferric chloride solution for 10-15 hours, and the temperature is maintained at 2-5°C; finally, the surface of the hydrogel is washed with deionized water to obtain a polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel; the amount of pyrrole used is 0.5-10vol% of the volume of the hydrogel; and the concentration of the ferric chloride solution is 0.5-2 mol / L.

2. Use of the polyacrylamide-sodium alginate-polypyrrole composite conductive hydrogel as claimed in claim 1 in a sensor.

3. The use according to claim 2, characterized in that: The sensor is a tensile strain sensor, and the specific assembly steps are: cutting the composite conductive hydrogel into a suitable size, connecting copper wires at both ends with conductive silver glue, connecting the copper wires to a digital multimeter to measure resistance, and attaching and fixing the hydrogel to the part to be tested. The resistance of the composite conductive hydrogel changes with the deformation of the test part.

4. The use according to claim 3, characterized in that: The sites include any of the fingers, wrists, elbows, knees and throat.

Citation Information

Patent Citations

  • Preparation method for sodium alginate-acrylamide-based hydrogel

    CN103396562A